Furtum and manus/potestas - Sirks, A (Brill Academic Publishers, 2013)
The nature of furtum has been subjected to various interpretations, often with the assumption that this delict changed in nature between the Twelve Tables and end of the 2nd century A.D. It is submitted here that the delict was originally an intrusion upon the power (manus, potestas, dominium) of the pater familias and in its most acute form (furtum manifestum) punished with a religious sanction, viz. treating the fur as sacer. The same sanction is found in the Twelve Tables for other delicts, connected with the power of the pater familias. Since manifest furtum always implied that the fur was caught red-handed, desacralisation of the delict led to a reduction of this constellation to a mere being caught in the act. Assuming this to have been the original nature of furtum explains the forms of furtum usus and possessionis. © 2013 Koninklijke Brill NV, Leiden.